Molecular and entomological surveillance of malaria vectors in urban and rural communities of Benguela Province, Angola - Gonçalo Alves; Arlete Dina Troco; Gonçalo Seixas; Rebecca Pabst; Alfredo Francisco; Cani Pedro; Luzala Garcia; José Franco Martins; Sergio Lopes (Parasites & Vectors, 2024)
Abstract Background Malaria is a major public health problem in Angola, with Anopheles gambiae sensu lato (s.l.) and An. funestus s.l. being the primary vectors. This study aimed to clarify the information gaps concerning local Anopheles mosquito populations. Our objectives were to assess their abundance, geographical dispersion, and blood-feeding patterns. We also investigated their insecticide resistance. Molecular methods were used to identify sibling species, determine the origin of blood meals, measure Plasmodium falciparum infection rates, and detect the presence of knockdown resistance (kdr) mutations. Methods Adult mosquitoes were collected indoors using CDC light traps from nine randomly selected households at two sentinel sites with distinct ecological characteristics. The samples were collected from 1 February to 30 June 2022. Anopheles mosquitoes were morphologically identified and subjected to molecular identification. Unfed Anopheles females were tested for the presence of P. falciparum DNA in head and thorax, and engorged females were screened for the source of the blood meals. Additionally, members of An. gambiae complex were genotyped for the presence of the L1014F and L1014S kdr mutations. Results In total, 2226 adult mosquitoes were collected, including 733 Anopheles females. Molecular identification revealed the presence of Anopheles coluzzii, An. gambiae senso stricto (s.s.), An. arabiensis, and An. funestus s.s. Notably, there was the first record of An. coluzzii/An. gambiae s.s. hybrid and An. vaneedeni in Benguela Province. Plasmodium falciparum infection rates for An. coluzzii at the urban sentinel site and An. funestus s.s. at the rural site were 23.1% and 5.7%, respectively. The L1014F kdr mutation was discovered in both resistant and susceptible An. coluzzii mosquitoes, while the L1014S mutation was detected in An. gambiae s.s. for the first time in Benguela Province. No kdr mutations were found in An. arabiensis. Conclusions This study provides valuable insights into the molecular characteristics of malaria vectors from the province of Benguela, emphasising the need for continuous surveillance of local Anopheles populations regarding the establishment of both kdr mutations for tailoring vector control interventions. Graphical abstract